Radar detection of the brine extent at McMurdo Ice Shelf, Antarctica, and its control by snow accumulation. Issue 13 (13th July 2016) - Grima, Cyril; Greenbaum, Jamin S.; Lopez Garcia, Erika J.; Soderlund, Krista M.; Rosales, Arami; Blankenship, Donald D.; Young, Duncan A.
Abstract: We derive the surface density and brine infiltration depth/extent at McMurdo Ice Shelf, Antarctica, from combined analysis of radar profiles and radar statistical reconnaissance of the surface from 2011 to 2012 austral summer airborne observations. Most of the brine boundaries appear controlled, directly or indirectly, by the snow accumulation pattern. The infiltration is bounded westward by an ablation area and resides just above the pore close‐off depth over most of its extent. The eastern brine limit matches a light‐snow corridor, suggesting a reversed pressure gradient at depth that might sharply slow down the infiltration. Brine into ice is confirmed at the deepest locations north and east of Williams Field. The ice‐ocean interface is undetected west of the infiltrated zone, except in localized patches. We hypothesize this echo‐free zone to be due to high scattering below the surface, possibly from a network of accreted ice and/or ice platelets at the ice‐ocean interface. Key Points: We map the brine extent, surface density, and roughness over McMurdo Ice Shelf Brine horizontal and vertical extent is controlled by snow accumulation An echo‐free zone might localize scattering from accreted ice or ice platelets